2021
DOI: 10.1177/21582440211054479
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance and Gender Differences: A Study of College and University Teachers From Karnataka

Abstract: Teaching responsibilities in today’s higher education sector are increasingly demanding. Apart from the focus on the quality of teaching-learning activities, teachers of today are evaluated for their active involvement in professional and societal growth. Women in academia shoulder equal responsibilities as of men, but in India, women play multiple roles in the non-work setting unlike men. The primary objective of this cross-sectional study was to find out the gender difference in Work-Life Balance (WLB) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…e quality inspection of college teachers is an important part of the construction of college teachers. In order to quantitatively analyze the problems existing in college teachers, different indicators are used to analyze them [17,18]. e first-level indicators mainly include: professional ethics, professional quality, research tasks, research summary, and research environment [19,20].…”
Section: Quality Monitoring and Evaluation Of College Teachersmentioning
confidence: 99%
“…e quality inspection of college teachers is an important part of the construction of college teachers. In order to quantitatively analyze the problems existing in college teachers, different indicators are used to analyze them [17,18]. e first-level indicators mainly include: professional ethics, professional quality, research tasks, research summary, and research environment [19,20].…”
Section: Quality Monitoring and Evaluation Of College Teachersmentioning
confidence: 99%
“…The results that support the conclusions and discussions of this study show that empowering leaders can explicitly improve job satisfaction of employees in an academic setting. Due to high extent of competitiveness in this sector ( Muijs and Harris, 2003 ; Bouwmeester et al, 2021 ; Mayya et al, 2021 ), leaders’ role become more vital in maintaining an environment, where teachers can develop their professional skills while being satisfied of work settings and communications and interactions with their supervisors. With a focus on LMX and SET, empowered teachers are more likely to have their job satisfaction improved.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous studies on gender differences in WLB, EE, and WB have been inconsistent. For example, Vithanage and Arachchige found that female teachers scored slightly higher on WLB than male teachers [ 41 ], while other studies showed that male teachers had better WLB than female teachers [ 40 ]. Some studies found that female college teachers had higher WB scores than male teachers [ 44 , 45 ], while other studies found that college teachers’ perceptions of WB showed no significant gender difference [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research on gender differences in WLB, WB, and EE among college teachers is inconsistent. Some studies have found that male teachers had stronger perceptions of WLB than female teachers [ 38 , 39 , 40 ], while other studies found that male teachers’ perceptions of WLB were weaker than those of female teachers [ 41 ], and yet others found no gender difference [ 42 , 43 ]. Similarly, some studies have shown that women have stronger perceptions of WB than men [ 44 , 45 ], but another study found no gender difference [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation